The Perceptual and Cognitive Processes That Govern Egg Rejection in Hosts of Avian Brood Parasites - Hanley, Daniel; Rutledge, Samantha L.; Villa, Juliana (Frontiers in Ecology and Evolution, 2021)
Hosts of avian brood parasites are under intense selective pressure to prevent or reduce the cost of parasitism. Many have evolved refined egg discrimination abilities, which can select for eggshell mimicry in their parasite. A classic assumption underlying these coevolutionary dynamics is that host egg recognition depends on the perceivable difference between their own eggs and those of their parasite. Over the past two decades, the receptor noise-limited (RNL) model has contributed to our understanding of these coevolutionary interactions by providing researchers a method to predict a host’s ability to discriminate a parasite’s egg from its own. Recent research has shown that some hosts are more likely to reject brown eggs than blue eggs, regardless of the perceived differences to their own. Such responses suggest that host egg recognition may be due to perceptual or cognitive processes not currently predictable by the RNL model. In this perspective, we discuss the potential value of using the RNL model as a null model to explore alternative perceptual processes and higher-order cognitive processes that could explain how and why some hosts make seemingly counter-intuitive decisions. Further, we outline experiments that should be fruitful for determining the perceptual and cognitive processing used by hosts for egg recognition tasks.